1989
DOI: 10.1016/0095-8956(89)90016-6
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial reconstruction problems

Abstract: A general technique for tackling various reconstruction problems is presented and applied to some old and some new instances of such problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 7 publications
1
60
0
Order By: Relevance
“…In Section 3 we showed that finite subsets of S 1 are 6-reconstructible under the action of SO (1). In [32] we show that a similar result for S n−1 would prove Conjecture 1.…”
Section: Further Questionsmentioning
confidence: 95%
See 4 more Smart Citations
“…In Section 3 we showed that finite subsets of S 1 are 6-reconstructible under the action of SO (1). In [32] we show that a similar result for S n−1 would prove Conjecture 1.…”
Section: Further Questionsmentioning
confidence: 95%
“…We define a pointed configuration C, x to be a coloured configuration in style (1), that is, a finite multiset C together with one distinguished element x ∈ supp(C), which has colour 1. An oriented configuration is, similarly, a coloured configuration in style (1, 1).…”
Section: The Methods Of Featuresmentioning
confidence: 99%
See 3 more Smart Citations